The Spanish Socialist Workers' Party: 145 years of history and new challenges - Grantseva Ekaterina (Латиноамериканский исторический альманах)
In 2024, the Spanish Socialist Workers' Party celebrated 145 years of existence. The PSOE is a political long-liver, one of the oldest left-wing parties in the world, which has skillfully adapted to the needs of a transforming society, accepting new challenges and seeking opportunities for productive work. The historical path of the PSOE is a path accompanied by doubts, criticism, jealousy, denial and reproaches. This was the case a century ago, when the PSOE agreed to collaborate with the Primo de Rivera regime, and the same situation re-mains today, when the government of Pedro Sánchez is forced to balance and seek support, receiving endless reproaches for populism, corruption and incompetence. It is also certain that the history of the PSOE is the history of Spain of the last century and a half, where the party participated not as a witness, but as one of the main characters.